2017
DOI: 10.3329/uhj.v12i1.34016
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum Uric Acid in-hospital Mortality and Morbidity in Patients with acute Myocardial Infarction

Abstract: Coronary artery disease (CAD) is one of the leading causes of death in the world and also in Bangladesh. This study was carried out to evaluate that Serum uric acid is a prognostic tool in acute myocardial infarction. In this study, 108 AMI cases were enrolled. All the patients were treated and managed identically by conventional standard management protocol. During hospital stay, patients were assessed for any kind of clinical outcomes e.g good recovery, mortality and morbidity (acute LVF, cardiogenic shock, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…But none of the patients of both groups developed mechanical complication. In this regards Hossain et al, (2016) [12], found that cardiogenic shock and acute left ventricular failure were signifi cantly more frequent in hyperuricemia group compared to normal serum uric acid level group (p=0.037 and p=0.004 respectively) whereas arrhythmia and heart block did not differ signifi cantly between two groups (p=0.545 and p=0.629 respectively). The difference may be because of inclusion of all acute Myocardial Infarction cases irrespective of STEMI and NSTEMI in their study but in this study only NSTEMI were included.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…But none of the patients of both groups developed mechanical complication. In this regards Hossain et al, (2016) [12], found that cardiogenic shock and acute left ventricular failure were signifi cantly more frequent in hyperuricemia group compared to normal serum uric acid level group (p=0.037 and p=0.004 respectively) whereas arrhythmia and heart block did not differ signifi cantly between two groups (p=0.545 and p=0.629 respectively). The difference may be because of inclusion of all acute Myocardial Infarction cases irrespective of STEMI and NSTEMI in their study but in this study only NSTEMI were included.…”
Section: Discussionmentioning
confidence: 95%
“…This study is discrepant regarding Killip class and raised serum uric acid from that of Biswas et al This study demonstrated that in-hospital mortality was 7.0% of all NSTEMI with 10.0% patients in group A and 4.0% patients in group B. In-hospital mortality was higher in group A than that of group B but did not reach the level of signifi cance (p>0.05). Hossain, et al (2016) [12], reported in-hospital mortality of acute MI was 7.3% with 14.3% of patients with raised uric acid level and 3% of patients with normal uric acid level. In-hospital mortality of acute MI was signifi cantly higher in patients with raised uric acid level than normal uric acid level (p=0.020).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that in-hospital mortality was 7.0% of all NSTEMI with 10.0% patients in group A and 4.0% patients in group B. In-hospital mortality was higher in group A than that of group B but did not reach the level of significance (p>0.05). Hossain et al, (2016) reported in-hospital mortality of acute MI was 7.3% with 14.3% of patients with raised uric acid level and 3% of patients with normal uric acid level [12]. In-hospital mortality of acute MI was significantly higher in patients with raised uric acid level than normal uric acid level (p=0.020).…”
Section: Discussionmentioning
confidence: 98%
“…In this regards Hossain et al, (2016) found that cardiogenic shock and acute left ventricular failure were significantly more frequent in hyperuricemia group compared to normal serum uric acid level group (p=0.037 and p=0.004 respectively) whereas arrhythmia and heart block did not differ significantly between two groups (p=0.545 and p=0.629 respectively) [12]. The difference may be because of inclusion of all acute Myocardial Infarction cases irrespective of STEMI and NSTEMI in their study but in this study only NSTEMI were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation